Analytical Study Of Speed Average On Liner Movements - Najah, Yasser (Journal of Physical Education, 2010)
There are two laws for Average speed yet one of those two is rarely used by researchers thus the researcher aimed at identifying the importance of applying this rarely used law compared to the other law. The first law, which is frequently used by researchers, is (Speed Average S1+S2/2) while the second law, which is less used by researchers, is (speed Average = Total Distance/Total Time). So as to show which law is more appropriate for measuring speed Average for linear movements as a biomechanical indicator we assumed two different speed for an athlete riding a bicycle. We changed the distances and times of these two speeds by increasing gradually and consistently so as the value of the two speeds remain the same. The researcher concluded the following: 1. There is a difference in the values of speed between the two laws. 2. The second law is the best law as a biomechanical indicator because the first law depends on the change in speed only while the second law depends on the changes in distances and times that cause the speed. 3. The increase in speed in the second law in an indicator of an increase in distance and time for the heist speed while the decrease in speed in the second law indicates increase in distance and speed for the lowest speed. Finally the researcher recommends educating students of Physical Education College who are interested in biomechanics so as to be able to identify the differences between the two laws and which one is the best to be used